A code-independent generalized actuator line model for wind farm aerodynamics over simple and complex terrain. (August 2017) - Rai, Raj K.; Gopalan, Harish; Sitaraman, Jayanarayanan; Mirocha, Jeffrey D.; Miller, Wayne O.
Abstract: Actuator line model representations of wind turbines reduce the simulation cost of wind farm aerodynamics relative to blade geometry resolving simulations. However, most implementations are code specific and may not have proper load balancing when run in parallel. Here, a generalized actuator line model (GALM) is developed to overcome this implementation drawback of existing approaches. The GALM can be coupled to any existing microscale solver with minimal or no modifications. The coupling of our GALM model with the open-source microscale code CgWind is used to demonstrate both its ease of use and fidelity. The results obtained from the coupled-model simulations are validated for both isolated turbine in wind tunnel experiments and measurements in offshore wind farm. Finally, an operational wind farm over complex terrain is demonstrated. The simulations show that wake meandering and power production are strongly influenced by terrain impacts. Access information for obtaining the code is provided.